A Preliminary result on the rGO functionalization as counter-electrode in dye-sensitized solar cells (DSSC). (August 2019) - Arsyad, Waode Sukmawati; Wardianto, Ahmad; Variani, Visca Inda; Ilmawati, Waode Sitti; Agusu, La; Hidayat, Rahmat
Abstract: In the effort of replacing Platinum (Pt) based counter-electrode (CE) for reducing fabrication cost in the dye-sensitized solar cell (DSSC), we synthesized rGO powder from graphite bar (commercially available) using modified Hummer's method with an introduction of microwave irradiation. rGO was attached to the FTO surface by dissolving it in the solvent with the addition of ethyl cellulose (ES) following by two-step annealing process. rGO solution was deposited by spin coating technique with different thickness namely 1 layer rGO (A1), 5 layer rGO (A2), 10 layer rGO (A3) and 15 layer rGO (A4) followed by an annealing process, and the reference cell was assigned as A5 (using Pt). From the thin film resistance measurement using the four-probe method and conductivity calculation, the conductivity decreased as the rGO layer becomes thicker, namely from (0.58 to 0.42, 0.07 and 0.03) S/cm for A1, A2, A3, and A4 in consecutive order. From the photovoltaic measurement, we found that the utilization of rGO as a catalyst in CE increased the efficiency of the cell from 3.82% (A5) to 4.52% (A1). Furthermore, increasing the thickness of rGO layer from A1 (2.1 μm) to A2 (10.5 μm) also increased the efficiency from 4.52% to 5.89%, further increasing on the layer thickness A3 (21 μm) to A4 (31.5 μm) reduced the conversion efficiency to 2.57% and 0.33%. The highest conversion efficiency achieved for the cell with 10.5 μm thickness of CE, specifically A2. Further investigation of the influence of CE thickness and conductivity to the internal parameters of the DSSC must be done in order to gain a much better understanding of this result.